2023
DOI: 10.1007/s10570-023-05268-8
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the compression strength of spacers made of high-density pressboard used in power transformers under the influence of thermal ageing

Abstract: The structural components inside power transformers are commonly made of high-density pressboard, due to its suitable mechanical and dielectric properties. Among these components are the spacers used in the windings of transformers, which are subjected to compressive loading during operation. The spacers are immersed in dielectric liquid and subjected to high temperatures and chemical reactions during the lifespan of the transformer, which result in the degradation of their dielectric and mechanical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Reference [18] investigated the impact of cushion blocks on the axial winding strength and of bracing ribs on the radial winding strength, with specific consideration of factors such as the number and width of cushion blocks. References [19,20] indicated that, over the transformer's lifespan, cushion blocks were immersed in dielectric fluid and exposed to high temperatures, thermal aging, and chemical reactions, resulting in the degradation of their dielectric and mechanical properties and weakening the transformer short-circuit resistance. In references [21,22], a two-dimensional simulation was established and the leakage flux and stress distribution of high-and low-voltage winding were analyzed; short-circuit tests were carried out and it was pointed out that the electromagnetic force generated by the fault current might lead to instability in and the collapse of the winding.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [18] investigated the impact of cushion blocks on the axial winding strength and of bracing ribs on the radial winding strength, with specific consideration of factors such as the number and width of cushion blocks. References [19,20] indicated that, over the transformer's lifespan, cushion blocks were immersed in dielectric fluid and exposed to high temperatures, thermal aging, and chemical reactions, resulting in the degradation of their dielectric and mechanical properties and weakening the transformer short-circuit resistance. In references [21,22], a two-dimensional simulation was established and the leakage flux and stress distribution of high-and low-voltage winding were analyzed; short-circuit tests were carried out and it was pointed out that the electromagnetic force generated by the fault current might lead to instability in and the collapse of the winding.…”
Section: Introductionmentioning
confidence: 99%